Volume of Martian midlatitude glaciers from radar observations and ice flow modeling. Issue 8 (27th April 2015) - Karlsson, N. B.; Schmidt, L. S.; Hvidberg, C. S.
Abstract Numerous glacier‐like forms have been identified in the midlatitudes of Mars, and within recent years the acquisition of radar sounding data has revealed that the features are chiefly composed of water ice. Here we use radar observations in combination with ice flow models and inverse methods to calculate the volume of ice present at the midlatitudes of Mars. In order to obtain ice thicknesses, we infer the yield stress of the ice deposits, and we find that they are consistently lower than those of most terrestrial glaciers. We estimate the present ice volume of lobate debris aprons (identified by Levy et al. (2014)) on Mars to correspond to 1.55 · 105 km3 with an uncertainty of 25%. This corresponds to a global ice cover of 1.1m. Thus, the water ice found at midlatitudes is an important water reservoir, and an important part of the global surface ice budget.